The Correlation Between Self Care Management and Blood Sugar Levels in Type 2 Diabetes Melitus Patient in The Working Area of The Kedaton Health Center - Nur Aisyah, Tiara; Khasanah, Uswatun; Marfuati, Sri (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2026)
Diabetes Mellitus is a group of metabolic diseases characterized by hyperglycemia that occurs due to abnormalities in insulin secretion, insulin action, or both. Uncontrolled DM progresses to complications. A way to prevent complications is self-care management. To analyze the correlation between self-care management and the blood sugar levels in type 2 diabetes mellitus patients in the working area of Kedaton Health Center. An analytical observational study with a cross-sectional design. Data were collected by completing a questionnaire and measuring blood sugar levels. The sample consisted of 158 respondents, selected using a purposive sampling technique. The analysis test used the Spearman correlation test. There are 98 respondents (62.0%) with poor self-care management and 60 respondents (38.0%) with good self-care management. The majority of respondents have uncontrolled blood sugar levels, namely 132 respondents (83.5%). The results of the Spearman correlation test showed a significant correlation between self-care management and blood sugar levels in type 2 diabetes mellitus patients in the working area of Kedaton Health Center (p-value = 0.002), with a weak positive correlation (r = 0.242). There is a significant correlation between self-care management and blood sugar levels in type 2 diabetes mellitus patients in the working area of Kedaton Health Center. The worse self-care management of the respondents, the more uncontrolled the blood sugar levels will be (³180 mg/dL).